In vitro magnetohydrodynamics system for modulating cell migration. (1st March 2023) - Gebreyesus, Eyerusalem A; Park, Alice; Guldberg, Robert E; Ong, Keat Ghee
Abstract: Fluid shear stress (FSS) is an important parameter that regulates various cell functions such as proliferation and migration. While there are a number of techniques to generate FSS in vitro, many of them require physical deformation or movement of solid objects to generate the fluid shear, making it difficult to decouple the effects of FSS and mechanical strains. This work describes the development of a non-mechanical means to generate fluid flow and FSS in a 2D in vitro setting. This was accomplished with a magnetohydrodynamic (MHD) pump, which creates liquid flow by generating a Lorentz force through the interaction between an electric field and an orthogonal magnetic field. The MHD pump system presented here consisted of trapezoidal prism-shaped magnets, a pair of platinum electrodes, and a modified petri dish. The system was validated and tested on an in vitro wound model, which is based on analyzing the migration of fibroblast cells through an artificially created scratch on a confluent cell culture surface. Experiments were performed to a control group, an electric field only group, and a group that was subject to fluid flow with the application of both electric field and magnetic field. Results show that fibroblast cells that experienced fluid shear have higher wound closure rate compared to the control group and the electric field only group. The data shows that the MHD pump can be a great tool to study FSS in vitro . Furthermore, due to its fluid flow generation without mechanical force, this system can be adapted and implemented to study the role of FSS and electric field on wound healing in vivo .